Five Hours Total Sleep Deprivation Does Not Affect CA1 Dendritic Length or Spine Density - Brodin, Alvin T. S.; Gabulya, Sarolta; Wellfelt, Katrin; Karlsson, Tobias E. (Frontiers in Synaptic Neuroscience, 2022)
Sleep is essential for long term memory function. However, the neuroanatomical consequences of sleep loss are disputed. Sleep deprivation has been reported to cause both decreases and increases of dendritic spine density. Here we use Thy1-GFP expressing transgenic mice to investigate the effects of acute sleep deprivation on the dendritic architecture of hippocampal CA1 pyramidal neurons. We found that five hours of sleep deprivation had no effect on either dendritic length or dendritic spine density. Our work suggests that no major neuroanatomical changes result from a single episode of sleep deprivation.